Perbandingan Efektivitas Leflunomide dengan Methotrexate untuk Terapi Artritis Rematoid - Suryoadji, Kemal Akbar; Wibowo, Pramesti Kusumadini (Cermin Dunia Kedokteran, 2024)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by symmetrical joint involvement and extra-articular manifestations. Methotrexate and leflunomide are disease modifying anti-rheumatic drugs(DMARD) and use as treatment options for rheumatoid arthritis. This report aims to compare the effectiveness of leflunomide with methotrexate as therapy for rheumatoid arthritis. Methods: Literature search was carried out through three electronic databases: PubMed, Cochrane, and EBSCOHost with specific keywords based on PICO. Selection was in accordance with inclusion and exclusion criteria based on the clinical question. Selected literature was critically reviewed using an adapted instrument from the University of Oxford’s CEBM. Result: One systematic review and meta-analysis literature by Alfaro-Lara, et al, (2017) was obtained. The results showed a trend towards methotrexate in achieving response according to American College of Rheumatology (ACR20) (0.88 [95% CI: 0.74-1.06]; p = 0.18), reduction in joint swelling was greater with methotrexate (-0.82 [95% CI: 0.24-1.39]; p = 0.006), no significant difference in joint pain reduction (p>0.05). Liver enzyme elevations were more frequent with leflunomide (0.38 [0.27-0.53]; p = 0.007); gastrointestinal (GI) complaints were more frequent with methotrexate (1.44 [1.17-1.79]; p = 0.0007), no significant difference in the incidence of non-severe infections. Conclusion: Leflunomide has the same efficacy as methotrexate for RA therapy; more reduction of joint swelling with methotrexate. Leflunomide was associated with greater increases in liver enzymes, but fewer GI complaints.